The improvement of critical thinking skill by using flipped classroom based e-module on circulation system material for the students at senior high school - Samsi, Irnayanti Fadhillah; Djukri, Djukri; Radhisa, Fitri Qalbina (Universitas Ahmad Dahlan, 2024)
The improvement of students critical thinking skill can be carried out in using innovative teaching material to achieve competence acquired. The aims of this research is to know the appropriateness accuracy, and effectiveness of flipped Classroom based E-module on circulation system material at XI SMA. The researcher uses R & D methodology with ADDIE development model through the stages. Analysis, design, development, implementation and evaluation The research subject is from the material scholars and media scholars. The instrument that used in this research are questionnaire, data analysis, that uses Likert scale. The results of this research indicates that the product is appropriately used to based on the material scholars and media scholars with the number is 97,91% (very appropriate) and the assessment of media scholar with the number 91,25% (very appropriate) based on the biology teacher assessment that E-Module is practical to use it with the number 100% (very practically) and the results of test little scare with the number 89,06% (very practical), and effective to improve students critical thinking skill based on N-gain score with 0.58 score.